A Case of Loose Anagen Hair Syndrome in a Southeast Asian Boy - Kanchana Leerunyakul; Poonkiat Suchonwanit (Karger Publishers, 2019)
Loose anagen hair syndrome is an uncommon hair disorder, particularly in non-Caucasian children. We report the case of a 13-year-old Thai boy who presented with a single patch of hair thinning on the frontal scalp with excessive shedding, and the hairs did not grow long. Microscopic examination showed naked anagen bulbs with ruffling of the cuticle, which is compatible with loose anagen hair syndrome. To our knowledge, there is no reported case in Southeast Asian children.